2015
DOI: 10.17507/tpls.0510.19
|View full text |Cite
|
Sign up to set email alerts
|

The Interference of First Language and Second Language Acquisition

Abstract: Abstract-One of the most important and fascinating aspects of human development is language acquisition. The present review summarizes some difficulties that second language learners may face to learn English. It has tried to find out factors that play an important role in the acquisition of second language. It is a popular belief that first language has an effect on the second language acquisition, and it is claimed that L1 can interfere with the acquisition of L2. It is also believed that the role of L1 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(96 citation statements)
references
References 12 publications
3
85
0
8
Order By: Relevance
“…They have a habit to transfer their mother tongue knowledge in the process of target language acquisition. Derakhshan and Karimi (2015) believe that when the learners are asked to speak they incline to transfer the forms of their mother tongue to the target language. The phonological difference between Sundanese and English language becomes the crucial issue to the learners.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…They have a habit to transfer their mother tongue knowledge in the process of target language acquisition. Derakhshan and Karimi (2015) believe that when the learners are asked to speak they incline to transfer the forms of their mother tongue to the target language. The phonological difference between Sundanese and English language becomes the crucial issue to the learners.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The interference of the mother tongue might be one of the reasons as mentioned by Nik et al (2010) and Derakhshan & Karimi (2015) who investigated the relation between first language and second language acquisition. They confirmed that the problem of students' writing performance is related to their first language.…”
Section: Context Of the Problemmentioning
confidence: 98%
“…They have observed that by and large researchers are agreed that the role of the native language in learning the second language depends on some similarities and dissimilarities between the two languages. In [24], the author investigated how the Spanish students learn and process the new content word in English as their second language. The limitation of their work is that they do not report convincingly on their findings, so it is difficult to assess their contribution.…”
Section: Related Workmentioning
confidence: 99%